White blood cell profiles in amphibians help to explain disease susceptibility following temperature shifts. (December 2017) - Greenspan, Sasha E.; Bower, Deborah S.; Webb, Rebecca J.; Berger, Lee; Rudd, Donna; Schwarzkopf, Lin; Alford, Ross A.
Abstract: Temperature variability, and in particular temperature decreases, can increase susceptibility of amphibians to infections by the fungus Batrachochytrium dendrobatidis (Bd). However, the effects of temperature shifts on the immune systems of Bd-infected amphibians are unresolved. We acclimated frogs to 16 °C and 26 °C (baseline), simultaneously transferred them to an intermediate temperature (21 °C) and inoculated them with Bd (treatment), and tracked their infection levels and white blood cell profiles over six weeks. Average weekly infection loads were consistently higher in 26°C-history frogs, a group that experienced a 5 °C temperature decrease, than in 16°C-history frogs, a group that experienced a 5 °C temperature increase, but this pattern only approached statistical significance. The 16°C-acclimated frogs had high neutrophil:lymphocyte (N:L) ratios (suggestive of a hematopoietic stress response) at baseline, which were conserved post-treatment. In contrast, the 26°C-acclimated frogs had low N:L ratios at baseline which reversed to high N:L ratios post-treatment (suggestive of immune system activation). Our results suggest that infections were less physiologically taxing for the 16°C-history frogs than the 26°C-history frogs because they had already adjusted immune parameters in response to challenging conditions (cold). Our findings provide a possible mechanistic explanation for observations that amphibians are more susceptible to Bd infection following temperature decreases compared to increases and underscore the consensus that increased temperature variability associated with climate change may increase the impact of infectious diseases. Highlights: We assessed frog immunity after infection and a temperature increase or decrease. Cold-acclimated frogs had active immune systems before and after treatment (increase). Hot-acclimated frogs had active immune systems only after treatment (decrease). Cold acclimation may prime the immune system for some challenges of infection. This helps explain high levels of disease susceptibility after temperature decreases.